FACTORS AFFECTING THE EFFICIENCY OF PEDAGOGICAL PROCESSES ORGANIZED IN NON-GOVERNMENT GENERAL EDUCATION SCHOOLS - Maxsudov Sardor (International Scientific and Current Research Conferences, 2023)
This article presents an analysis of factors affecting the effectiveness of pedagogical processes organized in non-state secondary schools.